2021
DOI: 10.1021/acs.jchemed.1c00718
|View full text |Cite
|
Sign up to set email alerts
|

Problem and Solution of UV–Vis Time-Based Measurements of a Chemical System Involving Gas Product: Application to the Bray–Liebhafsky Oscillatory Reaction

Abstract: Ultraviolet (UV)−visible (Vis) spectroscopy is widely used in all modern laboratories as a routine method of analysis. The monitoring of chemical reactions in an aqueous solution involving a gas product is a demanding task but particularly for oscillatory reactions which are obtainable in a narrow concentration range. In this work, the optimization of experimental conditions for UV−Vis measurements of the Bray− Liebhafsky (BL) oscillatory reaction producing oxygen was done by using an internal standard. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It has been reported that the reaction turns yellow due to the presence of iodine and faintly changes hue. Some experiments report periodic evolution of oxygen from the solution [4]. However, drawing on our own, admittedly limited, experimental work [5], we have found that the solution turns yellow after an induction period but no subsequent visually distinguishable periodic colour change was seen.…”
Section: Introductionmentioning
confidence: 66%
“…It has been reported that the reaction turns yellow due to the presence of iodine and faintly changes hue. Some experiments report periodic evolution of oxygen from the solution [4]. However, drawing on our own, admittedly limited, experimental work [5], we have found that the solution turns yellow after an induction period but no subsequent visually distinguishable periodic colour change was seen.…”
Section: Introductionmentioning
confidence: 66%
“…Classroom demonstrations of oscillatory chemical reactions have become a valuable pedagogical tool to introduce students to a variety of chemical concepts including kinetics, thermodynamics and catalysis . Over the past 50 years, nonlinear chemical dynamics has been the subject of numerous articles in this Journal . Such works span experimental demonstrations of oscillations and waves through the BZ and BR reactions, ,,,,, the mercury beating heart, the gas evolution oscillator, the chemiluminescent oscillator, , pH oscillators, the salt-water oscillator, , the explosion oscillator, and the Liesegang rings, to the theoretical presentation of the foundations of nonlinear dynamics, ,,,, and nonequilibrium thermodynamics . Most of these classroom demonstrations focused on oscillations in stirred systems and propagating waves in unstirred systems.…”
Section: Introductionmentioning
confidence: 99%